Probing the Role of Melanocortin Type 1 Receptor Agonists in Diverse Immunological Diseases - Spana, Carl; Taylor, Andrew W.; Yee, David G.; Makhlina, Marie; Yang, Wei; Dodd, John (Frontiers in Pharmacology, 2019)
Background The melanocortin α-melanocyte stimulating hormone (α-MSH), an endogenous peptide with high affinity for the melanocortin 1 receptor (MC1r), has demonstrated prevention and reversal of intestinal and ocular inflammation in animal models. Preclinical studies were performed to determine whether two MC1r receptor agonists, PL-8177 and PL-8331, exhibit actions and efficacy similar to α-MSH in preventing and reversing intestinal and ocular inflammation. Methods Both PL-8177 and PL-8331 were assessed in a Eurofins LeadProfilingScreen selectivity panel including 72 in vitro assays. PL-8177 was evaluated in an in vitro assay using human whole blood stimulated by lipopolysaccharide to determine inhibition of tumor necrosis factor alpha (TNF-α); for comparison, adrenocorticotrophic hormone (ACTH) and α-MSH were used as positive controls. PL-8177, dosed at 0.5 µg, 1.5 µg, and 5.0 µg, was assessed in a cannulated rat model of dinitrobenzene sulfonic acid (DNBS)-induced bowel inflammation and versus vehicle and oral sulfasalazine. PL-8177 was also dosed at 0.3 mg/kg/mouse injected intraperitoneally versus untreated controls and α-MSH treatment in mice with experimental autoimmune uveitis (EAU). PL-8331 at 3 dose levels, 3 times daily, was evaluated in a murine model of scopolamine-induced dry eye disease (SiccaSystem™ model), compared with twice-daily Restasis® and Xiidra®. Results Both PL-8177 and PL-8331 demonstrated no significant activity at the 10 μᴍ level in any of the 72 in vitro assays. PL-8177 inhibited lipopolysaccharide-induced TNF-α to a similar degree as ACTH and α-MSH. In the DNBS rat model of bowel inflammation, PL-8177 was significantly superior to untreated controls at all 3 doses (P<0.05) in reducing bowel inflammation parameters, with effects similar to sulfasalazine. In the murine EAU model, PL-8177 significantly reduced retinal inflammation scores versus untreated controls (P = 0.0001) over 3 to 5 weeks, and to a similar degree as α-MSH. In the murine scopolamine-induced model of dry eye disease, PL-8331 reduced corneal fluorescein staining scores at all doses, significantly (P = 0.02) for the highest dose (1 x 10-5 mg·mL-1), and similarly to Restasis®; Xiidra® demonstrated no effect. Conclusions The MC1r receptor agonists PL-8177and PL-8331exhibited actions similar to those of α-MSH in preventing and reversing intestinal and ocular inflammation in preclinical disease models.